2017
DOI: 10.1377/hlthaff.2017.0061
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities In Surgical Mortality: The Gap Appears To Have Narrowed

Abstract: Despite substantial attention to the greater likelihood of poor clinical outcomes among black versus white surgical patients, little is known about whether racial disparities in postoperative mortality in the United States have narrowed over time. Using nationwide Medicare inpatient claims data for the period 2005-14, we examined trends in thirty-day postoperative mortality rates in black and white patients for five high-risk and three low-risk procedures. Overall, national mortality trends improved for both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
8
48
0
Order By: Relevance
“…Costs were identified for the 15 most common medical discharge diagnoses (acute myocardial infarction, pneumonia, congestive heart failure, arrhythmia, esophageal or gastric disease, chronic obstructive pulmonary disease, urinary tract infection, renal failure, gastrointestinal tract bleeding, hip fracture, metabolic disorder, respiratory tract disease, chest pain, stroke, and sepsis) and 6 common complex surgical procedures previously used to study costs and quality of surgical care (hip replacement, colectomy, coronary artery bypass grafting, endovascular abdominal aortic aneurysm repair, pulmonary lobectomy, and open abdominal aortic aneurysm repair). 17 , 21 , 22 All costs were attributed to the hospital at which the index stay occurred regardless of the site of subsequent care (eg, readmission to a different hospital was attributed to the index hospital). The costs of care for hospitalizations ending in transfer (n = 20 710 [1.7%]) were assigned to the original hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Costs were identified for the 15 most common medical discharge diagnoses (acute myocardial infarction, pneumonia, congestive heart failure, arrhythmia, esophageal or gastric disease, chronic obstructive pulmonary disease, urinary tract infection, renal failure, gastrointestinal tract bleeding, hip fracture, metabolic disorder, respiratory tract disease, chest pain, stroke, and sepsis) and 6 common complex surgical procedures previously used to study costs and quality of surgical care (hip replacement, colectomy, coronary artery bypass grafting, endovascular abdominal aortic aneurysm repair, pulmonary lobectomy, and open abdominal aortic aneurysm repair). 17 , 21 , 22 All costs were attributed to the hospital at which the index stay occurred regardless of the site of subsequent care (eg, readmission to a different hospital was attributed to the index hospital). The costs of care for hospitalizations ending in transfer (n = 20 710 [1.7%]) were assigned to the original hospital.…”
Section: Methodsmentioning
confidence: 99%
“…A survey of chairmen at black-serving hospitals found that, when compared with non–black-serving hospital boards, these chairpersons report less expertise with quality-of-care issues and are less likely to give high priority to quality of care. 35 An analysis 36 of racial disparity in surgical mortality found that although gaps between black and white patients have narrowed overall, improvements were less likely among hospitals that served the highest proportion of minority patients. Overall, our findings suggest that similar systemic differences between MSHs and non-MSHs may be associated with the differences in receipt of palliative care among underserved minority patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two social risk factors used in this article, dual eligibility and race, are generally available and accurately measured in claims data . These two factors capture patient attributes for which there is strong evidence of substantial disparities in health outcomes . Related to this is the potential heterogeneity of effect of social risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…34 These two factors capture patient attributes for which there is strong evidence of substantial disparities in health outcomes. [11][12][13][14][15] Another practical limitation is that we did not account for cooccurrence of social risk factors. Some patients were both dual eligible and African American and, thus, either effect may have reflected in part that of the other risk factor.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation